Posisi Amicus Cureae Dalam Tata Peradilan Indonesia - Dewa Gede Edi Praditha (Madani: Jurnal Ilmiah Multidisiplin, 2023)
In the Indonesian legal system, recognizing the term amicus curiae or which literally means friend of the court, this study examines the position and status of amicus curiae in the Indonesian criminal procedural law order, through normative juridical research, through statutory approach methods. The results of the study found that amicus curiae in the Indonesian judiciary did not yet have a standard structure and components so that its position and position were still uncertain, this was because there was no specification of the regulations governing amicus curiae, amicus cureae itself was not the opinion of witnesses or expert witnesses, but only outside opinion into consideration of the panel of judges.